Use of A Hydroalcoholic Extract of Moringa oleifera Leaves for the Green Synthesis of Bismuth Nanoparticles and Evaluation of Their Anti-Microbial and Antioxidant Activities - Das, Prince Edwin (2020)
The employment of plant extracts in the synthesis of metal nanoparticles is a very attractive approach in the field of green synthesis. To benefit from the potential synergy between the biological activities of the Moringa oleifera and metallic bismuth, our study aimed to achieve a green synthesis of phytochemical encapsulated bismuth nanoparticles using a hydroalcoholic extract of M. oleifera leaves. The total phenolic content in the M. oleifera leaves extract used was 23.0 ∓ 0.3 mg gallic acid equivalent/g of dried M. oleifera leaves powder. The physical properties of the synthesized bismuth nanoparticles were characterized using UV-Vis spectrophotometer, FT-IR spectrometer, TEM, SEM, and XRD. The size of the synthesized bismuth nanoparticles is in the range of 40.4–57.8 nm with amorphous morphology. Using DPPH and phosphomolybdate assays, our findings revealed that the M. oleifera leaves extract and the synthesized bismuth nanoparticles possess antioxidant properties. Using resazurin microtiter assay, we also demonstrate that the M. oleifera leaves extract and the synthesized bismuth nanoparticles exert potent anti-bacterial activity against Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus, and Enterococcus faecalis (estimated MIC values for the extract: 500, 250, 250, and 250 μg/mL; estimated MIC values for the bismuth nanoparticles: 500, 500, 500, and 250 μg/mL, respectively). Similarly, the M. oleifera leaves extract and the synthesized bismuth nanoparticles display relatively stronger anti-fungal activity against Aspergillus niger, Aspergillus flavus, Candida albicans, and Candida glabrata (estimated MIC values for the extract: 62.5, 62.5, 125, and 250 μg/mL; estimated MIC values for the bismuth nanoparticles: 250, 250, 62.5, and 62.5 μg/mL, respectively). Thus, green synthesis of bismuth nanoparticles using M. oleifera leaves extract was successful, showing a positive antioxidant, anti-bacterial, and anti-fungal activity. Therefore, the synthesized bismuth nanoparticles can potentially be employed in the alleviation of symptoms associated with oxidative stress and in the topic treatment of Candida infections.